THE AGGLUTINATION REACTIONS OF THE MORGAN BACILLUS NO. 1 - Kligler, I. J. (The Rockefeller University Press, 1919)
The study of the cultural and agglutinating reactions of seventeen strains of Morgan bacilli is reported. The cultures were obtained from different sources. Culturally all the strains were identical. Antigenically they were highly diversified. The sera produced against some strains have marked agglutinating power for other strains, but absorption tests showed that the cross-agglutinations were often due to group agglutinins. While no conclusion can be drawn regarding the pathogenic significance of this bacillus, the wide diversities of antigenic properties raise the question as to the specific relationship of the various cultures met with as well as their relation to a definite class of pathological processes in man.